Excessive sulfur oxidation in endoplasmic reticulum drives an inflammatory reaction of chondrocytes in aging mice - Chen, Kun; Zhang, Xianzuo; Li, Zhi; Yuan, Xingshi; Fu, Daijie; Wu, Kerong; Shang, Xifu; Ni, Zhe (Frontiers in Pharmacology, 2022)
Osteoarthritis, as a common joint disease among middle-aged and elderly people, has many problems, such as diverse pathogenesis, poor prognosis and high recurrence rate, which seriously affects patients' physical and mental health and reduces their quality of life. At present, the pathogenesis of osteoarthritis is not completely clear, and the treatment plan is mainly to relieve symptoms and ensure basic quality of life. Therefore, it is particularly urgent to explore the pathogenesis of osteoarthritis. Protein, as organic macromolecule which plays a major role in life activities, plays an important role in the development of disease. Through protein omics, this study found that with the increase of age, excessive sulfur oxidation occurred in endoplasmic reticulum of chondrocytes, which then drove the occurrence of inflammatory reaction, and provided a direction for the follow-up molecular targeted.